Le savoir-faire des femmes imragen du littoral mauritanien à l’épreuve de la mondialisation - Sébastien Boulay (Revue d'anthropologie des connaissances)
Since the begining of the 20th century, mauritanian littoral imrâgen products, made of yellow mullet, have aroused interest amongst western people and have been subjected to several promotion initiatives. These past or present interventions, either guided by economic, ecological, or “development” goals, show themselves in a confrontation between imrâgen’s know-how and foreign know-how, by technical innovations more or less suitable depending on their relevance and appropriateness to local manufacturing conditions, and by the use of global recognition intruments and networks. This text aims at questioning this confrontation through the description and the analysis of a recent intervention of “requalification” of Banc d’Arguin National Park imrâgen women products, led by two international nature conservation NGOs.